Study guides

☆☆

Q: What is 26 equals 3b - 2 -7b?

Write your answer...

Submit

Related questions

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7

3b -2 =7 b+4

If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.

Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5

If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================

3b + 6 = 12 3b = 6 b = 2

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

N=3.1

b^2 - 7b + 12 = b^2 - 4b - 3b + 12 = b(b -4) -3(b - 4) = (b - 3)(b - 4)

First lets set up the equation.12 - 7b + 10b = 18.Now lets combine all like terms on the left hand side.12 - 7b + 10b = 1812 + 3b = 18Now lets combine all like terms using the like terms on the left side and on the right side.12 + 3b = 18-12 -123b = 6Now lets divided (since the 3 is being multiplied to the b).3b/3 = 6/3So your final answer is:b = 2

3b + 2a = 2 and -2 + a = 8 -2 + a = 8 can be rearranged to show a = 8 + 2 = 10 (Effectively 2 has been added to both sides.) As a = 10, the value for a can now be substituted in the equation 3b + 2a = 2 3b + 2x10 = 2 : 3b + 20 = 2 this can be rearranged to show 3b = 2 - 20 = -18 and dividing both sides by 3 gives b = -6.

20+3b = 20 + 3(-6) = 20-18 = 2

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

2a + 7b = -13a - 7b = -5The system of equations can be solved by elimination:2a + 3a = -65a = -6a = -6/5substitute the value of a in any of the two original equations to find the value of b:2(-6/5) + 7b = -1-12/5 + 1 = -7b-7/5 = -7bb= 1/5

With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)

12b2 - 8b = 0 4b(3b-2) = 0 4b = 0 and 3b-2 = 0 4b = 0 and 3b = 2 b = 0 and 2/3

The question is worded amibiguously. Do you mean 3(7b)-2, or 3(7b-2)? 3(7b) - 2: 2 = 21b 2/21 = b 3(7b -2): 21b - 6 = 0. 21b = 6 b = 6/21 = 2/7.

Write down both equations (I'll label them (1) and (2)):(1) a = 3b - 4(2) a + b = 16Pass b to the left side of the equation (1):(1) a - 3b = -4(2) a + b = 16Multiply (1) by -1:(1) -a + 3b = 4(2) a + b = 16Add down both equations:-a + 3b + a + b = 4 + 164b = 20b = 5Replace b in (2):a + 5 = 16a = 11

b2 - 7b - 6b = -4(-4)2 - 7(-4) - 6 = 16 +28 - 6 = 38

It is: 52/2 = 26

No. 7b - 2b = 5b

26

2 times 13 equals 26. 1 times 26 also equals 26.

6x - 3b + 8 = 16.Since you cannot simplify the equation, the answer is 6x - 3b = 8.However, if you would like to find x, you can substitute b with '0':6x - 3b + 8 = 166x - 3b = 86x - 3(0) = 86x = 86 6x = 1.33 or 1(1/3)If you want to find b, you can substitute x with '0':6x - 3b + 8 = 166x - 3b = 86(0) - 3b = 8-3b = 8-3 -3b = -2.66 or -2(2/3)